Electronic commerce (E-Commerce) to increase the efficiency of managing small and medium enterprises (SME) in production of Pathum Thani Province - Naknil, Pornchanok; Chansom, Nakamol (Mahachula Academic Journal, 2023)
The purposes of this research were (1) to study about the application of electronic commerce (E-Commerce) to increase the efficiency of SME business management in the production area, (2) to apply the results of the study of e-commerce to developing SMEs for production efficiency, it is the documentary research, as studying and researching from research articles; academic articles, documents, textbooks related to electronic commerce to increase the efficiency of small and medium enterprises (SME) management in production. A questionnaire was used to collect data from a sample of small and medium enterprises entrepreneurs. In the area of Pathum Thani province during July - December 2021, a total of 400 cases were used by convenient random sampling. The information obtained will be analyzed using a statistical computer program. The research found that the use of e-commerce to increase quality efficiency. Is to find good quality raw materials. Choice of raw materials according to needs and production planning control Implementing e-commerce to optimize volume is to produce more products Production can take many forms and inventory management Implementing e-commerce to optimize time, customers can contact the company 24 hours a day to produce products on time. To go to market quickly and convenient to communicate with customers Implementing e-commerce to increase cost efficiency, It can be considered as helping to reduce the number of salespeople at the product.